The Effect of Nutritional Status on Mesiodistal and Bucco-Lingual (Palatal) Diameters of Primary Teeth among Five Years Old Kindergarten Children - Zaid S Ahmed; Ban S Diab (College of Dentistry/ University of Baghdad, 2016)
Background: Malnutrition in human life may adversely affect various aspects of growth at different stages of life. Teeth are particularly sensitive to malnutrition. Malnutrition may affect odontometric measurement involving tooth size dimensions. The aim of this study is to estimate the effect of nutrition on teeth size dimension measurements among children aged 5 years old. Materials and methods: This study was conducted among malnourished group in comparison to well-nourished group matching with age and gender. The present study included 158 children aged 5 years (78 malnourished and 80 well-nourished). The assessment of nutritional status was done by using three nutritional indicators, namely Height-for-age, Weight-for-age and Weight-for-height. Odontometric measurements including two different orientations. For both upper and lower study models, photographs were taken using special photographic apparatus for each child, and the data were then analyzed using special computer software. For primary dentitions, two linear measurements (mesiodistal and bucco/lingual or palatal) were utilized, representing tooth diameters for each tooth. Results: Among children aged 5 years, the findings revealed that all means of mesiodistal and bucco-lingual diameters values of maxillary and mandibular teeth were lower among malnourished than well-nourished groups with statistically significant, except for mesiodistal diameters of both canine and lateral incisor maxillary teeth, canine of mandibular teeth and for bucco-palatal diameters of central incisor of maxillary teeth, canine, lateral incisor and central incisor of mandibular teeth. Conclusions: Malnutrition effect on minimize the odontometric measurements (mesio-distal and bucco-lingual diameters) among children aged 5 years.